2020
DOI: 10.1007/s00205-020-01580-w
|View full text |Cite
|
Sign up to set email alerts
|

Continued Gravitational Collapse for Newtonian Stars

Abstract: The classical model of an isolated selfgravitating gaseous star is given by the Euler–Poisson system with a polytropic pressure law $$P(\rho )=\rho ^\gamma $$ P ( ρ ) = ρ γ , $$\gamma >1$$ γ > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…The solutions constructed in Theorem 1.3 (1 < γ < 4 3 ) are very different from the GW solutions (γ = 4 3 ), and owe their existence to a subtle balancing of the three dominant forces in the problem: inertia, pressure, and gravity. A completely different portion of the phase-space is populated by the so-called dust-like collapsing stars, which have been shown to exist in [12]. The solutions constructed in [12] do not honour the scaling invariance implied by (1.5), but are instead to a leading order approximated by the so-called dust solutions, which solve (1.1)-(1.2) without the pressure term p.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions constructed in Theorem 1.3 (1 < γ < 4 3 ) are very different from the GW solutions (γ = 4 3 ), and owe their existence to a subtle balancing of the three dominant forces in the problem: inertia, pressure, and gravity. A completely different portion of the phase-space is populated by the so-called dust-like collapsing stars, which have been shown to exist in [12]. The solutions constructed in [12] do not honour the scaling invariance implied by (1.5), but are instead to a leading order approximated by the so-called dust solutions, which solve (1.1)-(1.2) without the pressure term p.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…A completely different portion of the phase-space is populated by the so-called dust-like collapsing stars, which have been shown to exist in [12]. The solutions constructed in [12] do not honour the scaling invariance implied by (1.5), but are instead to a leading order approximated by the so-called dust solutions, which solve (1.1)-(1.2) without the pressure term p.…”
Section: Introduction and The Main Resultsmentioning
confidence: 99%
“…The nonlinear stability in the expanding case was shown in [13]. When 1 < γ < 4 3 the authors in [9] showed the existence of an infinite-dimensional class of collapsing solutions to the gravitational Euler-Poisson system. When one considers the Euler-Poisson system with an electric (instead of gravitational) force field, the dispersive nature of the problem becomes dominant.…”
Section: Isothermal Euler-poisson Systemmentioning
confidence: 99%
“…When the initial density is small and has compact support, Hadzic-Jang [31] constructed a class of global-in-time solutions of the 3-D CEPEs in the Lagrangian coordinates for γ = 1 + 1 k , k ∈ N\{1} or γ ∈ (1, 14 13 ). More recently, Guo-Hadzic-Jang [26] constructed an infinite-dimensional family of collapsing solutions of CEPEs (1.1). We also refer [44,54,56] for the local well-posedness of smooth solutions.…”
Section: Introductionmentioning
confidence: 99%